Peran Orang Tua terhadap Pendidikan Islam Anak Usia Dini - Zubairi, Zubairi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The roles and responsibilities of parents in pre-school age children in the perspective of Islam are very important and very important in the development and formation of children's character and education because at this time it is very vital (golden age) for children's growth and development, both in terms of physical growth, brain growth, and spiritual growth because at this time children will usually imitate what their parents do, whether their actions are good or bad. Therefore, at this time parents must pay more attention to their children and educate them on good and positive things so that they become children who are beneficial to society, devoted to their homeland and nation. The research method in this journal is carried out with a literature review by analyzing theoretical data about the role of parents in children's Islamic education from an early age with various sources so that a comprehensive thought is formed about how important the role of parents in the formation of children's Islamic education is carried out. since early stage. Every parent wants to educate their child well and successfully. They hope that their children have personality, faith, and piety to Allah SWT. A child who has a noble character is devoted to his parents, and is useful for himself, his family, society, homeland, country, and also his religion. Efforts to educate children must start as early as possible so that children grow and develop into intelligent children. One of the earliest and most basic efforts is praying to Allah SWT, asking that the child who will be entrusted to us later is intelligent and pious, and asking for instructions so that we are given the ability to nurture, maintain and educate him by the teachings of Islam. So with the role and responsibility of parents for children's Islamic religious education, children will become a successful generation in the hereafter and able to serve their parents, homeland, and nation.